Investigation of color values of inkjet and laserjet prints on recycled papers - (:unkn) unknown (My University, 2021)
The aim of this study is to compare laserjet printing and inkjet printing properties on recycled papers. In the study, we recycled reference papers prepared in accordance with the INGEDE 11p standard. After recycling the papers, we produced test papers in the laboratory environment and examined the physical and optical properties of the obtained papers. We applied calendering process at 100 oC temperature and 20 bar pressure on the obtained test papers. After this process, we printed trigromy color measurement scales with inkjet and laserjet printers on the test papers obtaine Finally, using the spectrophotometer, we determined the printing properties of both print types. When we examined the results, we determined that in most of the printability parameters, laserjet had a superior performance and was a more usable printing system. For example, while the inkjet cyan density value is 0.94, the laserjet is 1.05. While M + Y trapping value was 28.23 in inkjet, it was 92.20 in laserjet. For example, we found the Gloss value as 2.53 in inkjet and 4.23 in laserjet. While inkjet cyan print chroma value is 44.03, it is 48.09 in laserjet. In addition, we determined that laserjet printing reached a wider area as a color gamut. Based on the color measurement results of both printing types, we have determined that the printability of recycled papers is reasonable. We have determined with experimental results that laserjet printing produces better quality prints in a short time, especially in the office environment.